DISCURSOS MIDIÁTICOS SOBRE O DESASTRE DA SAMARCO: UMA ANÁLISE DAS REPORTAGENS NAS REVISTAS VEJA E CARTACAPITAL - FERRAZ, VINICIUS SUZIGAN (2018)
This research investigates, with the help of discourse analysis, the discursive strategies of Veja and CartaCapital online news reports shortly after the rupture of the Fundão and Santarém dams, owned by Samarco Mineração S.A., causing the greatest socio-environmental disaster in Brazil, in Bento Rodrigues sub-district, in the city of Mariana-MG, leaving 19 dead, an unknown number of injured and disappeared, and a trail of 600 kilometers of toxic mud until it disembogue into the Atlantic Ocean, already on the coast of the state of Espírito Santo. It is hypothesized that these news oganizations, in the way each of them reports the event on their online platforms, end up bringing their representations of the facts so as to emphasize, in times of political polarization, discourses legitimizing their editorial lines and practices on an acceptable ideological metric. In the field of theoretical references, in the part referring to methodology, this work dialogues with Dominique Maingueneau, among other authors working with AD. Among the main objectives of the work, we try to understand if the discursive strategies used by the magazines sediment and / or enable a way for this political polarization. In this way, the work is structured in three chapters: the first is to recount the stories that involved the Samarco disaster through official documents and sources; In the second one, the emphasis is on the theoretical-methodological questions of research, on the discussion of language and its imbrications with discourse and the media; in the third and last chapter, the attention is drawn to the quantitative analysis of what we have called the "great narrative" and qualitative, applying the French AD on the first two news reports published by each portal after the event. It is understood that the two magazines construct their narratives and discourses according to the hypothesis suggested here, legitimating in Veja a liberal-conservative discourse and, in CartaCapital, a progressive discourse, making possible ways for this political-ideological polarization.